Gold : Its Geological Nature, Origin And Occurrences In India - Banerjee, Dilip Kumar (Indian Science Cruiser, 1993)
The geological origin, nature of gold and its occurrences and history of mining in India are presented with global estimation of its amount in different countries of the world.